THU0139 Pharmacokinetics of fostamatinib in patients with impaired hepatic function: A phase I study. (23rd January 2014) - Martin, P.; Oliver, S.; Gillen, M.; Marbury, T.; Millson, D.
Abstract : Background: Fostamatinib (R788), a spleen tyrosine kinase inhibitor, is currently being developed as an oral therapy for patients with rheumatoid arthritis 1 . Once administered, fostamatinib is converted to its active moiety, R406. Hepatic metabolism plays the major role in R406 elimination, whereas renal excretion has a smaller contribution 2 . Consequently, hepatic impairment may have an effect on R406 pharmacokinetics (PK), possibly leading to a greater overall exposure. Objectives: To assess R406 PK in healthy and hepatically impaired subjects following a single dose of fostamatinib. Methods: A total of 32 volunteers were enrolled in the phase I study (NCT01222455 ); eight with mild hepatic impairment (Child-Pugh Class A), eight with moderate hepatic impairment (Child-Pugh Class B), eight with severe hepatic impairment (Child-Pugh Class C), and eight with normal hepatic function. At least four volunteers with mild hepatic impairment were dosed prior to the recruitment of any with moderate or severe hepatic impairment. Participants received a single 150-mg dose of fostamatinib, with blood samples collected up to 120-h post-dose for the determination of R406 plasma concentrations. Urine was collected from pre-dose to 48 h post-dose to determine R406 and N-glucuronide concentrations. Results: R406 Cmax values were 10–15% lower in all hepatically impaired groups when compared with the normal hepatic function group. Subjects with normal and severely impaired hepatic function had similar AUC and tmax . The mild and moderate hepatic impairment groups had a lower AUC, and later tmax, than subjects with normal and severe hepatic dysfunction. Urinary excretion of R406 was minimal. Glucuronidation of R406 was preserved in hepatically impaired subjects with the amount of R406 N-glucuronide excreted in urine higher in severely impaired subjects. Seventeen adverse events (AEs) were reported for 10 subjects but these were unrelated to increasing hepatic dysfunction. The most frequently reported AE was sinus congestion in two subjects in the moderate hepatically impaired group. No clinically relevant changes in transaminase levels were reported in subjects exposed to fostamatinib. Conclusions: Hepatic impairment did not affect the exposure of the active metabolite R406 to an extent that would be considered clinically relevant. Consequently, there is no expectation of a need for fostamatinib dose reduction in hepatically impaired subjects. References: Baluom M, et al. J Clin Pharmacol 2011;51:1310–1318. Sweeny DJ, et al. Drug Metab Dispos 2010;38:1166–1176. Disclosure of Interest: P. Martin Shareholder of: AstraZeneca Pharmaceuticals, Employee of: AstraZeneca Pharmaceuticals, S. Oliver Shareholder of: AstraZeneca Pharmaceuticals, Employee of: AstraZeneca Pharmaceuticals, M. Gillen Shareholder of: AstraZeneca Pharmaceuticals, Employee of: AstraZeneca Pharmaceuticals, T. Marbury: None Declared, D. Millson Shareholder of: AstraZeneca Pharmaceuticals, Employee of: AstraZeneca Pharmaceuticals